Relationship between job involvement, perceived organizational support, and organizational commitment with job insecurity: A systematic literature review - Hngoi, Chin Ling; Abdullah, Nurul-Azza; Wan Sulaiman, Wan Shahrazad; Zaiedy Nor, Norshaffika Izzaty (Frontiers in Psychology, 2023)
This paper reviews the literature on the relationship between job insecurity and job involvement, perceived organizational support, organizational commitment, and positional characteristics. The definition and conceptualization of the variables are discussed for clarity. Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) is conducted in this paper for systematic review. Nineteen articles on relationships with job insecurity are summarized and reviewed to determine the practical implications and areas to focus on in the future. Finally, this article provides shreds of evidence for the need to investigate the antecedents and consequences of job insecurity to increase productivity and reduce attrition.